Peranan World Food Programme (WFP) Melalui Program Food For Assets (FFA) Dalam Upaya Mengurangi Potensi Rawan Pangan Di Indonesia - Elin Dewanti (Universitas Komputer Indonesia, 2018)
This study was to determine the role of the World Food Programme (WFP) through the Food For Assets (FFA) in an effort to reduce the potential for food insecurity in West Nusa Tenggara 2008-2010. Researchers analyzed the various efforts made by WFP through the FFA in its efforts to reduce the potential for food insecurity in the region is categorized as having food insecurity in West Nusa Tenggara. Author of the research methods used in this study is qualitative method, aims to describe the facts relating to the problem under study. Most of the data collected through library research, online data retrieval, documentation, and interviews. The data was then analyzed with the theories and concepts in International Relations, among others, The Role of International Organizations, and Non-Traditional Security Issues. The results showed that the WFP has done its role as an international organization that focuses on food issues. WFP is providing food assistance to areas experiencing food insecurity in Indonesia, one of which is the West Nusa Tenggara. Such assistance is implemented in the form of FFA programs and activities to support efforts to reduce the potential for food insecurity in West Nusa Tenggara.